Three-dimensional time-of-flight secondary ion mass spectrometry imaging of primary neuronal cell cultures - Van Nuffel, Sebastiaan (2017)
Time-of-flight secondary ion mass spectrometry (ToF-SIMS) has proven its ability to characterise (in)organic surfaces, and is increasingly used for the characterisation of biological samples such as single cells. By combining ion imaging and molecular depth profiling it is possible to render 3D chemical images, which provides a novel, label-free way to investigate biological systems. Major challenges lie, however, in the development of data analysis tools and protocols that preserve the cell morphology. Here, we develop and employ such tools and protocols for the investigation of neuronal networks. One of the reasons 3D ToF-SIMS imaging of cells is underused is the lack of powerful data analysis tools as 3D ToF-SIMS measurements generate very large data sets. To address this issue, we developed a method that allows the application of principal component analysis (PCA) to be expanded to large 3D images making 3D ToF-SIMS image processing of whole, intact cells and cellular networks with multivariate analysis now accessible on a routine basis. Using this method, we are able to separate cellular material from the substrate and can then correct z-offsets due to the cells' topography resulting in a more accurate surface heightmap. The method also facilitates differentiation between cellular components such as lipids and amino acids allowing the cell membrane, the cytoplasm and the extracellular matrix (ECM) to be easily distinguished from one another.